2005
DOI: 10.1002/polb.20713
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydroxyl‐terminated poly(ether ether ketone) with pendenttert‐butyl groups and its use as a toughener for epoxy resins

Abstract: Hydroxyl-terminated poly(ether ether ketone) with pendent tert-butyl groups (PEEKTOH) was synthesized by the nucleophilic substitution reaction of 4,4 0difluorobenzophenone with tert-butyl hydroquinone with potassium carbonate as a catalyst and N-methyl-2-pyrrolidone as a solvent. Diglycidyl ether of bisphenol A epoxy resin was toughened with PEEKTOHs having different molecular weights. The melt-mixed binary blends were homogeneous and showed a single composition-dependent glass-transition temperature (T g ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 56 publications
4
37
0
Order By: Relevance
“…Data reveals that there is a marginal decrease in both tensile modulus and flexural modulus with the addition of PEEKMOH oligomer to the epoxy/DDS system. Similar observation was made by us earlier for epoxy-hydroxyl terminated tertiary butyl PEEK 24 and epoxy-hydroxyl terminated methyl PEEK systems. 23 It is known that the incorporation of clay into the epoxy matrix enhances tensile modulus and flexural modulus to a great extent.…”
Section: Fracture Toughness Tensile and Flexural Propertiessupporting
confidence: 83%
See 2 more Smart Citations
“…Data reveals that there is a marginal decrease in both tensile modulus and flexural modulus with the addition of PEEKMOH oligomer to the epoxy/DDS system. Similar observation was made by us earlier for epoxy-hydroxyl terminated tertiary butyl PEEK 24 and epoxy-hydroxyl terminated methyl PEEK systems. 23 It is known that the incorporation of clay into the epoxy matrix enhances tensile modulus and flexural modulus to a great extent.…”
Section: Fracture Toughness Tensile and Flexural Propertiessupporting
confidence: 83%
“…However, no evidence of drastic increase in fracture toughness was reported in the open literature for epoxy clay nanocomposites. On the other hand, more than 100% increase in fracture toughness was observed by us 23,24 and others [26][27][28][29][30][31][32] for the thermoplastic-toughened epoxy systems. Frohlich et al 33 reported the improved toughness in rubber-toughened hybrid epoxy nanocomposites compared with nanocomposite without rubber.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The phase separation that occurred by nucleation and growth mechanism was due to off-critical composition of the thermoplastic in liquid epoxy as calculated by Flory-Huggins model [57]. Similar observations were made by us earlier for PEEK-MOH-and PEEKTOH [hydroxyl terminated poly(ether ether ketone) with pendant tertiary butyl groups] toughened epoxy systems [8,12]. Here gelation followed by vitrification occurred after the phase separation.…”
Section: Scanning Electron Microscopesupporting
confidence: 80%
“…However, their brittle nature due to its high cross-link density and poor resistance to crack propagation limits the applications in advanced aerospace structures. To overcome this problem various Engineering thermoplastics like polyether sulfone [2,3], polycarbonate [4,5], polyethylene tere phthalate [6,7], poly ether ether ketone/hydroxyl terminated poly (ether ether ketone) with pendant methyl groups (PEEKMOH) [8,9], Poly ether ether ketone/hydroxyl terminated poly ether ether ketone with pendant tertiary butyl groups [10][11][12][13] or poly (cyanoarylene ether)/hydroxyl terminated poly arylene ether nitrile with pendant tertiary butyl groups [14,15] have been used as a toughness modifiers for epoxy resin without sacrificing other thermomechanical properties. However no evidence of improvement in modulus, gas barrier property and in coefficient of thermal expansion (CTE) was reported in the literature.…”
Section: Introductionmentioning
confidence: 99%